2001
DOI: 10.1111/j.1471-0528.2001.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Follow up after LLETZ: could schedules be modified according to risk of recurrence?

Abstract: Women aged > or = 50 with CIN at the margins of excision constituted a small minority high risk group (3%). Consideration should be given to repeat treatment of these women rather than surveillance. Women aged < 50 with complete excision of low grade CIN comprised 51% of the study group. These women were at low risk of recurrent CIN and might benefit from less intensive cytological surveillance following LLETZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
4
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 21 publications
3
45
4
10
Order By: Relevance
“…Approximately 15% of patients with CIN 2-3 that are treated by LEEP will experience a persistence/recurrence of their disease [12]. The significance of margin status as a predictor of disease persistence/recurrence is somewhat controversial [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. However, most studies have shown that CIN 2-3-positive margins on a LEEP or conization specimen correlate with an increased risk of recurrent/ persistent dysplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 15% of patients with CIN 2-3 that are treated by LEEP will experience a persistence/recurrence of their disease [12]. The significance of margin status as a predictor of disease persistence/recurrence is somewhat controversial [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. However, most studies have shown that CIN 2-3-positive margins on a LEEP or conization specimen correlate with an increased risk of recurrent/ persistent dysplasia.…”
Section: Introductionmentioning
confidence: 99%
“…La récidive est plus probable lorsque les marges endocervicales sont non in sano que dans les cas où les marges exocervicales sont atteintes [15,18,19] (NP4). Le statut non in sano des marges est un marqueur de récidives [10,[20][21][22][23] (NP4), mais il n'est pas très fiable [24][25][26][27] (NP2) car près de 65 % des patientes n'ont pas de lésion résiduelle dans cette situation.…”
Section: Marges Chirurgicalesunclassified
“…L'analyse cytologique effectuée après le traitement semble cependant avoir une sensibilité et une spécificité moins éle-vées que lors du dépistage initial. Sa principale faiblesse est le taux plus élevé de faux négatifs [20,22,44,45] (NP2) au cours de la période de suivi des traitements conservateurs des lésions du col. Les résultats de la cytologie dépendent d'une bonne qualité d'échantillonnage, peut-être plus difficile à obtenir en postopératoire, par ailleurs les résultats du test sont subjectifs avec des interprétations diagnostiques variables entre cytologistes.…”
Section: Méthodes Et Techniques Actuelles De Suivi Cytologieunclassified
“…Dans le cadre du suivi postconisation, la sensibilité et la spécificité de la cytologie sont encore inférieures à ce qui est observé dans les programmes de dépistage. Le principal problème est représenté par : le nombre élevé de faux négatifs des frottis en relation avec les variations de lecture interpathologistes et l'échan-tillonnage moins satisfaisant sur des cols traités [46,[50][51][52] ; qui pourrait être compensé par la répétition des frottis mais ce dernier point se heurte, d'une part, au manque de compliance des patientes au suivi cytologique à qui n'est que de 30 à 50 % et, d'autre part, à la diminution de spécificité [41].…”
Section: Cytologieunclassified